2012
DOI: 10.1080/07060661.2012.661767
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofTomato yellow leaf curl bigeminivirus(TYLCV) infection on tomato cell ultrastructure and physiology

Abstract: Tomato yellow leaf curl bigeminivirus was isolated in Kuwait and therefore designated as TYLCV-K. The virus was found to be transmitted by whiteflies (Bemisia tabaci Genn.), and produced the characteristic external symptoms on tomato (Solanum lycopersicum L.) test plants. Electron microscopy of ultra-thin sections of infected leaves showed alterations in the ultrastructure of some organelles and uneven thickenings of the cell wall of the phloem tissue associated with severe damage in chloroplasts and abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…11D, F). Similarly, disorganization of the membrane system of the chloroplasts in the infected mesophyll cells, breakdown of the envelope, damage of the cell wall, disappearance of starch grains or the appearance of large starch grains with an increase of plastoglobuli are indicative of infection [121][122][123]. Our results were also in agreement with Gabara et al [124] and Kozieł et al [125].…”
Section: Light and Transmission Electron Microscopy (Tem)supporting
confidence: 92%
“…11D, F). Similarly, disorganization of the membrane system of the chloroplasts in the infected mesophyll cells, breakdown of the envelope, damage of the cell wall, disappearance of starch grains or the appearance of large starch grains with an increase of plastoglobuli are indicative of infection [121][122][123]. Our results were also in agreement with Gabara et al [124] and Kozieł et al [125].…”
Section: Light and Transmission Electron Microscopy (Tem)supporting
confidence: 92%
“…Gene ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases are routinely used to annotate functions of differentially expressed genes (DEGs) in tomato plants. We focused on analysis of genes involved in cell wall biosynthesis as previous reports had shown that tomato leaves infected with TYLCV induced thickening of cell walls ( Montasser et al, 2012 ). We also sought to identify differentially expressed genes in hormone signaling pathways and secondary metabolite regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum TSC and TSP were recorded with Bion with foliar application followed by SA and infected control. Montasser et al (2012) Carbohydrates in leaves were significantly decreased in TYLCV isolates infected of tested plant cultivars as compared to healthy ones; this may be due to the defense effect of the plant against the virus infection where the strategy altered from defensive to survival as described by Khalil et al (2014). These results are in harmony with the findings of Radwan et al (2007), Gupta et al (2010).…”
Section: Discussionmentioning
confidence: 77%